The seed physiological potential of hybrid corn treated with insecticides and store in two environmental conditions - Baldiga Tonin, Rosane Fátima (2014)
Seed treatment is a widely disseminated practice in Brazilian cultural areas, which linked to other cultural practices, has contributed to the increase in productivity, cost reduction, final product improvement, environmental damage reduction as well as good seed protection in the field level and storage. The work had the objective to check the insecticide effect on the germination and vigor of the hybrid maize seeds, stored in two environmental conditions. The seeds were treated with three insecticides, identified as: Insecticide one (Thiametoxan); Insecticide two (Neonicotinoide) and Insecticide three [Neonicotinoide + (Imidaclopride+thiodicarbe)]. After being treated, the seeds were stored for a period of 270 days, in two different places, one with (10ºC) temperature and relative humidity (60%) and another under normal condition of storage. During this period evaluations were accomplished every 45 days, through germination and vigor tests. In addition to germination and cooling tests, sanitation analysis, seedling emergency and seed inoculation were carried out. After that the seeds were stored for a period of 30 days in environmental places with and without control of air condition. The results obtained allow to conclude that the maintenance of seed quality of hybrid maize, treated with insecticides, depends on the hybrid and chemical product used in their treatment and that the reduction in feasibility and vigor of seeds treated with thiametoxan is intensified due to the storage period extension.